A finite separating set for Daigle and Freudenburg's counterexample to Hilbert's Fourteenth Problem - Dufresne, Emilie; Kohls, Martin (Communications in algebra, 2010)
This article gives the first explicit example of a finite separating set in an invariant ring which is not finitely generated, namely, for Daigle and Freudenburg's 5-dimensional counterexample to Hilbert's Fourteenth Problem.
Published online: 20 Jan 2011
Gesehen am 20.02.2023